A microtubule-activated ATPase from sea urchin eggs, distinct from cytoplasmic dynein and kinesin. - Collins, C A (1986)
We report an ATPase activity, present in sea urchin egg cytosol, that is activated by microtubules. The activity sediments at 10 S in sucrose gradients and is clearly distinct from activities at 12 S and 20 S due to cytoplasmic dynein. Potent activation of the ATPase is observed when endogenous egg tubulin is induced to assemble with taxol or when exogenous taxol-stabilized pure brain tubulin microtubules or flagellar outer-doublet microtubules are added. No activation by tubulin subunits or taxol alone is detectable. In contrast to flagellar or cytoplasmic dynein, the microtubule-activated enzyme is unaffected by vanadate or by nonionic detergents and hydrolyzes GTP in addition to ATP. In contrast to kinesin, it cosediments with microtubules in the presence or absence of ATP. The microtubule-activated enzyme may have a role in microtubule-based motility.